(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we study the existence of mild solution for a class of impulsive partial neutral functional integrodifferential equation with unbounded delay by using Leray Schauder alternative fixed point theorem.